Clustering challenges in biological networks - Butenko, Sergiy; Chaovalitwongse, W. Art; Pardalos, P. M. (Panos M.), 1954- (World Scientific, 2009)
This text offers introductory knowledge of a wide range of clustering and other quantitative techniques used to solve biological problems.